Development of Basil Essential Oil (BEO) as a Novel Alternative to Prolong the Storage of Tomato (Lycopersicum esculentum L.) - Mira Elena Ionica; Felicia Tutulescu; Andrei Bita (Agriculture, 2022)
Antimicrobial compounds used as post-harvest treatment of fruit and vegetables can extend their shelf life by reducing the rate of microbial growth. Essential oils extracted from herbs or spices can also enhance shelf life due to their antimicrobial nature. Tomatoes harvested at consumption maturity were treated by spraying with aqueous solutions of basil essential oil (BEO) and glycerol in different concentrations (50, 100, 150, 200, 250 and 300 ppm) and stored by refrigeration at 8 <semantics>∘</semantics>C and 85% relative humidity. The BEO used was obtained by extraction from indigenous crops of Ocimum basilicum and was analyzed by GC-MS for discerning of the constituents present in it. The main components identified in BEO were: eucalyptol, linalool, estragol, eugenol methyl-cinamate, trans-<semantics>α</semantics>-bergamotene, germacrene D, <semantics>γ</semantics>-cadinene and T-cadinol. During storage, in order to highlight the effect of the applied treatment, the following were determined: dry matter (DM), total soluble content (TSS), total phenols content (TP), antioxidant activity (AOA), color, weight loss and total number of aerobic mesophilic bacteria (AMB) during storage. It has been shown that spraying the fruit with solutions of different concentrations of BEO has significant effects on weight loss, DM, TSS, TP, AOA, color and TAMB, during storage. The lowest TP value was found in the control and the variant treated only with 2.5% aqueous glycerol solution (52.18 mg/100 g fw GAE) and the highest value in the variants treated with concentrations of 200, 250 and 300 ppm BEO (54.37, 55.00 and 57.81 mg GAE/100 g fw). The highest AOA values were found in the 300 ppm BEO-treated variant (119.23 <semantics>μ</semantics>mol TE/100 g fw). Spraying tomatoes with aqueous solutions of glycerol 2.5% and BEO at a dose of 250 ppm prolongs their storage while maintaining their quality for fresh consumption.